Commodity price stabilisation and the developing countries - BROOK, E.; GRILLI, E.; WAELBROECK, J. (PSL Quarterly Review, 2014)
Developing countries have, for more than two decades, emphasised the adverse impact of prices and export revenue fluctuations on their economies. Despite the considerable effort that has gone into the study of the causes and effects of primary commodities’ price instability, progress in devising practical solutions and implementing them has been slow. The present article looks at commodity price stabilisation - defined as an operation intended to smooth out price fluctuations around the trend set by market forces - in terms of specific objectives and defines criteria for determining the primary commodities whose price stabilisation at the international level would benefit most the developing countries as producers or consumers. JEL: E31, E63, O23